Phenology of advanced selections of low-chilling peach trees in Urussanga, state of Santa Catarina - Martinello Back, Marina; Della Bruna, Emílio; Pola, Augusto Carlos; Belmonte Petry, Henrique; Bettio Marodin, Gilmar (Revista Ceres, 2023)
The objective of this study was to evaluate the influence of the environment and the genetic factor on the the phenology of 16 advanced selections of peachtrees in the municipality of Urussanga, state of Santa Catarina. The experiment was conducted in two areas (360 m and 220 m above sea level) in 2017, 2018, and 2019 harvests. The selections are part of the EPAGRI fruit breeding program. The dates of beginning, full, and end of flowering and budding, percentage of flowering, budding and effective fructification were determined. The standard model (number of hours with temperatures below 7.2 °C) was not the most suitable. Full flowering was anticipated by five days, on average over three years, at the highest altitude due to the greater accumulation of cold. The 16 selections were classified into three groups: early (harvest in October), medium (harvest in November), and late (harvest in December). It is concluded that the environment and the genetic factor influence the phenology of advanced peach selections. Being the first, it influences the periods of flowering and budding and the percentages of flowering, budding and effective fruiting. The second with emphasis the maturation cycle and the harvest period.